Pemerolehan Kosakata Anak Bahasa Anak Akibat Pengaruh Video Pemain Gim di Youtube - Asyatunnisa Adhitama Eka Putri; I Nyoman Suparwa; Anak Agung Putu Putra (Udayana University, 2023)
This research is entitled Acquisition of Children's Vocabulary Due to the Effect of Video Game Players on Youtube for children aged 4-8 in Rabakodo Village, Sarae Village, RT 09 RW 04 Kec. Wow, Kab. Bima, NTB. which aims to find out how to acquire children's vocabulary and the process of how they master it and to describe the application of Chomsky's genetic theory of cognitivism in acquiring children's vocabulary due to the influence of video game players on Youtube. This research is an interesting problem phenomenon for researchers in the field of psycholinguistics, this is an issue that is very impressive and difficult to prove. This research is included in the type of qualitative descriptive research. The method of data collection is done by the method of observing. The method of data analysis in this study used the matching method and the distributional method. In this study, the presentation of the results of data analysis used was informal. The analysis is carried out with a description of the explanation in simple words that are easy to understand and still use technical terminology. The results of this study are children aged 4-8 years have acquired nouns (mobile phone, monster, weapon, etc.), verbs (hit, play, dead, etc.), and adjectives (strong, crazy, far, etc.) quite well. The application of Chomsky's genetic theory of cognitivism in the acquisition of children's language vocabulary affected by video game players on YouTube distinguishes (language skills), performance (implementation or language processing), and language creativity in language acquisition.